RELIGIOUS EXTREMISM AND THE CRISIS OF INSECURITY IN NIGERIA: A PHILOSOPHICAL DISCOURSE - UGWU, Anayochukwu Kingsley; ENEH, Joseph Ogbunwani (IJRDO - Journal of Social Science and Humanities Research, 2022)
This paper sets out to discuss the effects of religious extremism and how they breed insecurity in Nigeria. This is apt following the fact that over the years, little or no concern has been given to religion as a major causative factor of insecurity crisis in Nigeria. Today, in as much as the question of insecurity is not exclusively a consequence of economic, political or tribal crisis, religion through extremists has been identified as a major factor. However, in addressing this issue, the paper raises certain questions to include: What end is expected from religion? What should be the primary force driving religion? Nevertheless, at the end of this research, it shall, through the exposition on religious influences in the country, prove that religion is a causative phenomenon to insecurity crisis in Nigeria. The paper shall also proffer solutions to these effects as it takes the discourse through comparative and expository methods in ethical and ontological dimensions.